Spinisternum castaneipictus Willemse, 1966 (Orthoptera: Tettigoniidae: Conocephalinae) from Papua New Guinea, with description of the male and remarks on the relationship - Ünal, Mustafa (Zootaxa, 2009)
In the present paper, the male of Spinisternum castaneipictus Willemse, previously unknown is described. The similarity of Spinisternum with other genera causes confusion in identification. This problem is discussed and similar species in different genera are compared. A key to species of Spinisternum and illustrations of S. castaneipictus are provided.